2021
DOI: 10.1152/ajpheart.00541.2021
|View full text |Cite
|
Sign up to set email alerts
|

The coronary and microcirculatory measurements in patients with aortic valve stenosis study: rationale and design

Abstract: Objective: Although coronary artery disease (CAD) is frequent in patients with aortic stenosis (AS), hemodynamic assessment of CAD severity in patients undergoing valve replacement for severe AS is challenging. Myocardial hypertrophic remodelling interferes with coronary blood flow and may influence the values of fractional flow reserve (FFR) and non-hyperemic pressure ratios (NHPRs). The aim is to investigate these effects on current CAD indices by comparing intra-coronary hemodynamics prior to, immediately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“… 12 Currently multiple trials on this topic are underway. The COMIC-AS study 13 investigates the acute and long-term effects of AV intervention on intra-coronary indices. Other trials are investigating physiology-guided PCI with CABG The TransCatheter Valve and Vessels Trial (TCW), angiography-guided PCI (FAITAVI), optimal timing of revascularization (TAVI-PCI), or medical management (NOTION-3) of CAD ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“… 12 Currently multiple trials on this topic are underway. The COMIC-AS study 13 investigates the acute and long-term effects of AV intervention on intra-coronary indices. Other trials are investigating physiology-guided PCI with CABG The TransCatheter Valve and Vessels Trial (TCW), angiography-guided PCI (FAITAVI), optimal timing of revascularization (TAVI-PCI), or medical management (NOTION-3) of CAD ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently, a small study has suggested that fractional flow reserve remains more stable when compared with resting full-cycle ratio after TAVI; however, more research is needed to confirm this. 4,5 In our opinion, it might have been better not to include the patients who underwent physiology-guided PCI or to analyze them as a separate group. This in order not to mix different methods of PCI selection and to evaluate the merit of angiography-guided PCI (which is currently the most frequent strategy to select lesions).…”
mentioning
confidence: 99%
“…Measurements were performed according to previously described standards. 1,2 In the open-chest model, 7 sheep underwent identical measurements while having direct and simultaneous assessment of flow with epicardial Doppler flow probes (gold standard) as a validation method. In addition to the animal measurements, in 41 patients undergoing routine microvascular assessment in clinical practice, CFR and IMR measurements were repeated after a 5-minute waiting time, recalibration, and rewiring of the same blood vessel by the same operator.…”
mentioning
confidence: 99%
“…Continuous coronary thermodilution measurements have already increased our understanding of the complex physiological changes in myocardial blood flow related to AS, which are essential for correct physiological assessment of the microcirculation and epicardial coronary artery disease in these patients. 2,4 The latter seems critical to improve patient outcomes in AS, since the presence of complex coronary artery disease in AS has been shown to be an independent predictor for worse cardiovascular survival after transcatheter aortic valve replacement. 5 Although MRR seems to be the best microvascular index, more human data are needed: (1) to determine normal values and define microvascular dysfunction and (2) to show a potential correlation between low MRR values and clinical outcomes or signs and symptoms of cardiac disease.…”
mentioning
confidence: 99%